STAT3 Contributes To Oncolytic Newcastle Disease Virus-Induced Immunogenic Cell Death in Melanoma Cells - Shao, Xiaoyan; Wang, Xueke; Guo, Xianling; Jiang, Ke; Ye, Tian; Chen, Jianhua; Fang, Juemin; Gu, Linaer; Wang, Sitong; Zhang, Guirong; Meng, Songshu; Xu, Qing (Frontiers in Oncology, 2019)
Background: Oncolytic viruses (OVs) are emerging as potent inducers of immunogenic cell death (ICD), releasing danger-associated molecular patterns (DAMPs) that induce potent anticancer immunity. Oncolytic Newcastle disease virus (NDV) has been shown to educe ICD in both glioma and lung cancer cells. The objective of this study is to investigate whether oncolytic NDV induces ICD in melanoma cells and how it is regulated. Methods: Various time points were actuated to check the expression and release of ICD markers induced by NDV strain, NDV/FMW in melanoma cell lines. The expression and release of ICD markers induced by oncolytic NDV strain, NDV/FMW, in melanoma cell lines at various time points were determined. Surface-exposed calreticulin (CRT) was inspected by confocal imaging. The supernatants of NDV/FMW infected cells were collected and concentrated for the determination of ATP secretion by ELISA, HMGB1 and HSP70/90 expression by immunoblot (IB) analysis. Pharmacological inhibition of apoptosis, autophagy, necroptosis, ER Stress and STAT3 (signal transducer and activator of transcription 3) was achieved by treatment with small molecule inhibitors. Melanoma cell lines stably depleted of STAT3 were established with lentiviral constructs. Supernatants from NDV-infected cells were intratumorally injected to mice bearing melanoma cells-derived tumors. Results: Oncolytic NDV induced CRT exposure, the release of HMGB1 and HSP70/90 as well as secretion of ATP in melanoma cells. Inhibition of apoptosis, autophagy, necroptosis or ER stress attenuated NDV/FMW-induced release of HMGB1 and HSP70/90. Moreover, NDV/FMW-induced ICD markers in melanoma cells were also suppressed by either treatment with a STAT3 inhibitor or shRNA-mediated depletion of STAT3. Of translational importance, treatment of mice bearing melanoma cells-derived tumors with supernatants from NDV/FMW-infected cells significantly inhibited tumor growth. Conclusions: Our data authenticate that oncolytic NDV/FMW might be a potent inducer of ICD in melanoma cells, which is amalgamated with several forms of cell death. We also show that STAT3 plays a role in NDV/FMW-induced ICD in melanoma cells. Together, our data highlight oncolytic NDV as propitious for cancer therapeutics by stimulatingan anti-melanoma immune response.